Predicting CBR values using gaussian process regression and meta-heuristic algorithms in geotechnical engineering - Wu, Xu; Yang, Feng; Huang, Shuchen (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2024)
The California Bearing Ratio (CBR) test is a vital tool in geotechnical engineering and is useful in controlled laboratory settings and dynamic field applications. It plays a pivotal role in determining the load-bearing properties of subgrade soil, which is essential for various construction projects, including retaining walls, highway embankments, bridge abutments, and earth dams. CBR values obtained from this test are fundamental for assessing soil strength and integrity, making it a cornerstone of geotechnical engineering. This paper presents an innovative method for predicting CBR values with high precision. It employs Gaussian Process Regression (GPR) to develop complex and highly accurate predictive models. These models encompass a wide range of soil characteristics, such as particle distribution, plasticity, linear shrinkage, and the type and quantity of stabilizing additives. The GPR model significantly improves predictive modeling accuracy by establishing robust relationships between these soil attributes and CBR values. Additionally, the study incorporates two advanced meta-heuristic algorithms, the Dynamic Arithmetic Optimization Algorithm (DAOA) and Leader Harris Hawk’s Optimization (LHHO), to enhance the precision of the predictive model. This collaborative effort resulted in the creation of three models: GPR + LHHO (GPLH), GPR + DAOA (GPDA), and GPR. The GPDA model stands out with exceptional predictive capabilities, achieving a remarkable R 2 value of 0.989 during training and an optimal RMSE of 1.488, confirming its precision and consistency. This innovative approach advances CBR prediction and reinforces the reliability of geotechnical engineering practices across diverse soil conditions, making it a significant contribution to the field.